Autophagy Contributes to Host Immunity and Protection against Zika Virus Infection via Type I IFN Signaling - Yuyi Huang; Yujie Wang; Shuhui Meng; Zhuohang Chen; Haifan Kong; Ting Pan; Gen Lu; Xuefeng Li (Hindawi Limited, 2020)
Recent studies have indicated that the Zika virus (ZIKV) has a significant impact on the fetal brain, and autophagy is contributing to host immune response and defense against virus infection. Here, we demonstrate that ZIKV infection triggered increased LC3 punctuation in mouse monocyte-macrophage cell line (RAW264.7), mouse microglial cell line (BV2), and hindbrain tissues, proving the occurrence of autophagy both in vitro and in vivo. Interestingly, manual intervention of autophagy, like deficiency inhibited by 3-MA, can reduce viral clearance in RAW264.7 cells upon ZIKV infection. Besides, specific siRNA strategy confirmed that autophagy can be activated through Atg7-Atg5 and type I IFN signaling pathway upon ZIKV infection, while knocking down of Atg7 and Atg5 effectively decreased the ZIKV clearance in phagocytes. Furthermore, we analyzed that type I IFN signaling could contribute to autophagic clearance of invaded ZIKV in phagocytes. Taken together, our findings demonstrate that ZIKV-induced autophagy is favorable to activate host immunity, particularly through type I IFN signaling, which participates in host protection and defense against ZIKV infection.